Juridical Analysis of Criminal Liability for Perpetrators of Child Neglect in Indonesia - Mujito, Mujito; Suwito, Suwito; Darmawan, Didit; Inama, Inama; Saadi, Nailil Izzati (Innovative: Journal Of Social Science Research, 2025)
Child neglect is a form of human rights violation that has a serious impact on the growth and development of children, both in terms of physical, psychological, and social aspects. This study aims to analyze the criminal liability of perpetrators of child neglect based on Law Number 35 of 2014 concerning Child Protection and identify obstacles in law enforcement of this case. The method used in this research is a normative legal approach by analyzing relevant laws and regulations as well as doctrinal studies of applicable legal practices. The results showed that although the regulation has regulated criminal sanctions for perpetrators, in its implementation there are still obstacles in proving the elements of intent and negligence. In addition, the weak supervision system and the low level of reporting from the public cause many cases of child neglect not to receive maximum legal handling. Therefore, stronger efforts are needed in the aspects of supervision, increasing legal awareness, and optimizing coordination between institutions in handling child neglect cases in order to provide more effective protection for children in Indonesia.